THE APPLICATION OF BALLISTIC PENDULUM FOR RESEARCHES OF SHOCK DURABILITY OF MATERIALS - Астанін, В.В.; Олефір, Г.О. (Science-based technologies, 2009)
Ballistic pendulum is designed for applications as a part of experimental installation for investigation of material impact strength. It provides an optimal material specimen fastening method for differentiating and making possible to register integral energy characteristics of the impact interaction process of accelerated to a certain velocity impacter and the specimen. It also allows the corresponding measuring unit data transfer to computer with the aim of their saving and following analysis. The measuring unit complex is a part of the ballistic pendulum system. Mathematical model of the obtained at the designed device usage impact process is analyzed. Workability of the device is experimentally proved.